Apis Mellifera Propolis Extract As A Stimulator Of Brain Cell Development (Study On Experimental Animals) - Mafruchati, Maslichah; Makuwira, Jonathan (CV. Nusantara Scientific Medical, 2022)
Apis mellifera could have potential as cell growth stimulator ability of the propolis. It also expected to increase the growth and proliferation of brain cells. This study aimed to analyze Apis mellifera Propolis Extract as a Stimulator of Brain Cell Development in Experimental Animals. This research is an experimental study using a completely randomized design (CRD) with 6 treatments and 4 replications. The research consisted of making Propolis Extract, Making Media (DMEM Stock Media, Washing Media, Culture and Treatment Media), Brain Cell Isolation and Culture, Observation of Culture Results (Cell Viability, Population Doubling Time, The results found that all treatments with propolis extract showed higher average viability than the control, which had average viability of 86.3%. Based on PDT (Population Doubling Time value), propolis extract has a good effect on brain cell growth, hence increasing cell proliferation. In addition, the confluent brain cells of rats given propolis extract had higher average confluency than those not given propolis extract. Propolis extract can protect neurons from damage by increasing the brain-derivatedneurotrophic factor (BDNF) gene expression in cell line neuron cultures.